2018
DOI: 10.1111/1759-7714.12792
|View full text |Cite
|
Sign up to set email alerts
|

Non‐canonical functions of the mitotic kinesin Eg5

Abstract: Kinesins are widely expressed, microtubule‐dependent motors that play vital roles in microtubule‐associated cellular activities, such as cell division and intracellular transport. Eg5, also known as kinesin‐5 or kinesin spindle protein, is a member of the kinesin family that contributes to the formation and maintenance of the bipolar mitotic spindle during cell division. Small‐molecule compounds that inhibit Eg5 activity have been shown to impair spindle assembly, block mitotic progression, and possess anti‐ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 79 publications
(92 reference statements)
0
19
0
Order By: Relevance
“…The wave swing is spread by the antirelaxation coordination but the mechanism of adjusting the synchronous swing of multiple cilia is not clear. In addition, the effectiveness of MCC is affected by a diversity of factors, including cilia numbers and their structure, humidity, temperature, age, pathogens, and environmental stimuli …”
Section: Structure and Function Of Airway Ciliamentioning
confidence: 99%
See 1 more Smart Citation
“…The wave swing is spread by the antirelaxation coordination but the mechanism of adjusting the synchronous swing of multiple cilia is not clear. In addition, the effectiveness of MCC is affected by a diversity of factors, including cilia numbers and their structure, humidity, temperature, age, pathogens, and environmental stimuli …”
Section: Structure and Function Of Airway Ciliamentioning
confidence: 99%
“…In addition, the effectiveness of MCC is affected by a diversity of factors, including cilia numbers and their structure, humidity, temperature, age, pathogens, and environmental stimuli. [25][26][27][28][29]…”
Section: Structure and Function Of Airway Ciliamentioning
confidence: 99%
“…At the same time, existing studies have shown that persistent inflammation can also trigger and exacerbate malignant tumors . These characteristics not only give researchers new ideas on how to treat cancer; for example, by inhibiting the activity of microtubule motor proteins, blocking mitosis or development of inflammatory factor‐related inhibitors (such as histone deacetylase 6 [HDAC] inhibitors), achieving the purpose of anticancer agents, they also provide valuable reference to assist with the early diagnosis of tumors . Electrochemical biosensor technology, as a new type technology of tumor detection, has achieved breakthrough results after decades of development.…”
Section: Discussionmentioning
confidence: 99%
“…HPV is a spherical DNA virus that stimulates the proliferation of squamous epithelial cells of skin mucosa in humans. [57][58][59][60][61] Infection of cervical epithelial cells with HPV leads to cervical cancer in women. 62 This is a result of a loss of cell adhesion and polarity, allowing the invasion and migration of tumor cells.…”
Section: Human Papilloma Virus (Hpv) and Adherens Junctionsmentioning
confidence: 99%
“…HPV is a spherical DNA virus that stimulates the proliferation of squamous epithelial cells of skin mucosa in humans . Infection of cervical epithelial cells with HPV leads to cervical cancer in women .…”
Section: Introductionmentioning
confidence: 99%